Beyond the conference: Singing our SSONG - Green, Corinne A.; Eady, Michelle J.; McCarthy, Marian; Akenson, Ashley B.; Supple, Briony; McKeon, Jacinta; Cronin, James G. R. (Teaching and Learning Inquiry, 2020)
The International Society for the Scholarship of Teaching and Learning (ISSOTL) annual conference presents an exciting opportunity to meet with international colleagues from diverse backgrounds and situations to commune on our common interest in the Scholarship of Teaching and Learning (SoTL). As with every ISSOTL conference, the enthusiasm for SoTL was palpable in Los Angeles in 2016. Rich discussions took place, networks were formed, and promises to keep in touch were made. Unfortunately, previous conference experiences have taught us that these good intentions often fall short once the conference bubble has burst and the reality of daily life sets in once more. In an attempt to circumvent this phenomenon, we—seven colleagues from three different countries—embarked on a research project that enabled us to maintain the relationships and fruitful discussions we had initiated at ISSOTL16. We established Small, Significant Online Network Group, or SSONG, inspired by a conference workshop on small significant networks. As a group, we met regularly online using Adobe Connect© and engaged in significant conversations around SoTL that were private, trustful, and intellectually intriguing. This article reflects our experiences in establishing and maintaining the group. We discuss how the group was formed; its alignment with the concept of small, significant networks; and the benefits and challenges we encountered. Four key principles of the group that have emerged will also be discussed in detail, enabling readers to consider how they could adapt the concept for their own purposes.